Strengthening student literacy about Asesmen Kompetensi Minimum (AKM) questions at MI Luqman Al-Hakim Slawi - Hasna’ Nadia Shalihah; Risris Hari Nugraha (Universitas Pendidikan Indonesia, 2023)
Literacy is still a study of unresolved issues in Indonesia. Until now, all parties are still organizing various programs to increase the literacy level of Indonesian society. An effective way to improve literacy is to start at the primary level. This service aims to strengthen the literacy level of students participating in AKM (Minimum Competency Assessment) from their understanding of AKM questions. It also aims to discover how to overcome the problems experienced by students. This service carries out a student literacy strengthening program based on understanding the AKM questions that have been worked on. So that if students find similar questions, they are expected to do it more quickly and precisely. This activity results in students needing help with AKM in literacy, such as taking a long time to read, needing to be more careful about details, and needing help answering reflection questions correctly. The obstacles in AKM in the field of numeration are the difficulty in understanding the meaning of the questions and the need for more proficiency in basic calculations. The solution to the problem above is to strengthen students' habits of reading and doing math problems because these two things are the most basic knowledge in the learning process and enhance literacy. Abstrak Literasi masih menjadi kajian isu yang belum terpecahkan di Indonesia. Sampai saat ini semua pihak masih mengerahkan beragam program untuk meningkatkan tingkat literasi masyarakat Indonesia. Cara yang efektif untuk meningkatkan literasi adalah dengan memulainya dari tingkat dasar. Pengabdian ini bertujuan untuk menguatkan tingkat literasi siswa peserta AKM (Asesmen Kompetensi Minimum) dari pemahamannya terhadap soal AKM. Juga bertujuan untuk mengetahui bagaimana solusi untuk mengatasi permasalahan-permasalahan yang dirasakan oleh para siswa. Pengabdian ini melaksanakan program penguatan literasi siswa berdasarkan pemahaman soal-soal AKM yang telah dikerjakannya. Sehingga apabila siswa menemukan soal-soal yang serupa diharapkan dapat mengerjakannya dengan lebih cepat dan tepat. Hasil dari kegiatan ini yaitu bahwa siswa memiliki kendala pada AKM bidang literasi, seperti membutuhkan waktu yang lama untuk membaca, kurang teliti pada hal-hal detail, dan belum bisa menjawab pertanyaan refleksi dengan baik. Adapun kendala dalam AKM bidang numerasi adalah kesulitan memahami maksud soal dan masih kurang mahir dalam perhitungan dasar. Solusi dari masalah di atas adalah dengan penguatan pembiasaan siswa dalam membaca dan mengerjakan soal berhitung, karena kedua hal tersebut merupakan pengetahuan paling mendasar dalam proses pembelajaran dan penguatan literasi. Kata Kunci: Asesmen Kompetensi Minimum; AKM; literasi siswa; penguatan literasi